Italy : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
Economic activity stagnated in the first half of 2003, but recent indicators point to a gradual recovery. On product markets, there was agreement that progress had been secured over recent years, but also that Italy continued to suffer from insufficient competition in a number of protected sectors. Consolidation, privatization, and improvements in risk management in recent years have helped the banking system weather the current economic slowdown. The authority for telecommunications has recently revised downward the price cap in the retail market.